The Growth of Paracoccus sp. SKG on Acetonitrile is Best Modelled using the Buchanan Three Phase Model (Journal of Environmental Bioremediation and Toxicology, 2015)
Organonitriles are carcinogenic and mutagenic. Bioremediation of acetonitrile, an organonitrile, has been touted as a more economical and feasible method compared to physical and chemical approaches. In this work, we model the growth of growth of Paracoccus sp. SKG on acetonitrile from published literature to obtain vital growth constants. These growth constants can only be accurately obtained from mathematical modelling of the growth curves using various available primary models such as logistic, Gompertz, Richards, Schnute, Baranyi-Roberts, Von Bertalanffy, Buchanan three-phase and more recently Huang models. The Buchanan three-phase model was chosen as the best model based on statistical tests such as root-mean-square error (RMSE), adjusted coefficient of determination (R2), bias factor (BF), accuracy factor (AF) andcorrected AICc (Akaike Information Criterion). Novel constants obtained from the modelling exercise would be useful for further secondary modelling implicating the effect of media conditions and other factors on the growth of this bacterium on acetonitrile.
Keywords: growth curve, mathematical model, acetonitrile-degrading, Buchanan-three-phase, statistical analysis